Stock Market Volatility, Consumption and Investment; An Evaluation of the Uncertainty Hypothesis Using Post-War U.S. Data - Burkhard Raunig; Johann Scharler (Oesterreichische Nationalbank (OeNB), 2011)
We estimate the effects of stock market volatility on the growth rates of durable consumption, non-durable consumption and invest- ment using post-war US data. Our results indicate that high levels of stock market volatility exert large adverse effects on the growth rates of investment and durable consumption, whereas the in uence on non-durable consumption growth is rather limited. The ordering of the magnitudes of the effects of stock market volatility across the three components of aggregate demand supports the idea that stock mar- ket volatility is closely related to uncertainty about future economic developments.
Keywords: E44; E20; E30; 330; uncertainty hypothesis; stock market volatility; consumption; investment